METODE KOMUNIKASI DA’WAH H. M. YUNAN NASUTION DI JAKARTA TAHUN 1967-1996 - Ujang Habibi; Fendi Irawanto (Jurnal Da'wah: Risalah Merintis, Da'wah Melanjutkan, 2025)
To determine the method of communication of H.M Yunan Nasution's da'wah in Jakarta from 1967 to 1996. Research Method: Qualitative. Research Results: H.M Yunan Nasution's Da'wah Communication Method in Jakarta. The method applied is a comprehensive and integrated method during da'wah in Jakarta through the Oral/Verbal method, namely oral such as lectures, religious studies, sermons, da'i training, and discussions. The written method is writing such as da'wah bulletins, translating Middle Eastern books, journals and publishing da'wah books and Islamic thought. The Nonverbal method is actions, examples. Such as the founder and leader of the Da'wah Council, training da'i, realizing da'wah values ​​in everyday life. Conclusion: H.M Yunan Nasution uses three approaches to the method of da'wah communication: Bil Lisan (lecture), Bil Kitabah (Da'wah Bulletin, Friday Sermon, Muhammad Rasulullah), and Bil Hal (establishing and being active in the Indonesian Islamic Da'wah Council).